Efficient activation of PAA by FeS for fast removal of pharmaceuticals: The dual role of sulfur species in regulating the reactive oxidized species - Yang, Shu-Run; He, Chuan-Shu; Xie, Zhi-Hui; Li, Ling-Li; Xiong, Zhao-Kun; Zhang, Heng; Zhou, Peng; Jiang, Feng; Mu, Yang; Lai, Bo (Water research (Oxford), 2022)
•Satisfactory degradation efficiency of pollutants was achieved by FeS/PAA system.•S(-II) and H2S (aq) played a significant role in Fe(II) regeneration.••OH played a dominant role in pharmaceuticals degradation.•The R-O• generated was supposed to be quickly consumed by sulfur specie.•Degradation products of three pharmaceuticals were successfully detoxified. As peracetic acid (PAA) is being increasingly used as an alternative disinfectant, efficient activation of PAA by low-cost and environmentally friendly catalysts over a wide pH range is potentially useful for simultaneous sterilization and pharmaceutical degradation in wastewater, such as hospital wastewater. In this study, peracetic acid (PAA) was successfully activated by low-cost and environmental-friendly FeS (25 mg/L) for efficient oxidative removal of three pharmaceuticals over a wide pH range (3.0∼9.0) as indicated by 80∼100% removal rate within 5 min. As expected, Fe(II) rather than sulfur species was the primary reactive site for PAA activation, while unlike the homogeneous Fe2+/PAA system with organic radicals (R-O·) and ·OH as the dominant reactive oxidized species (ROS), ·OH is the key reactive species in the FeS/PAA system. Interestingly and surprisingly, in-depth investigation revealed the dual role of sulfur species in regulating the reactive oxidized species: (1) S(-II) and its conversion product H2S (aq) played a significant role in Fe(II) regeneration with a result of accelerated PAA activation; (2) however, the R-O· generated in the initial seconds of the FeS/PAA process was supposed to be quickly consumed by sulfur species, resulting in ·OH as the dominant ROS over the whole process. The selective reaction of sulfur species with R-O· instead of ·OH was supported by the obviously lower Gibbs free energy of CH3COO· and sulfur species than ·OH, suggesting the preference of CH3COO· to react with sulfur species with electron transfer. After treatment with the FeS/PAA system, the products obtained from the three pharmaceuticals were detoxified and even facilitated the growth of E. coli probably due to the supply of numerous carbon sources by activated PAA. This study significantly advances the understanding of the reaction between PAA and sulfur-containing catalysts and suggests the practical application potential of the FeS/PAA process combined with biotreatment processes. [Display omitted]